PREVALENCE AND RISK FACTORS OF UNDERWEIGHT FOR ADOLESCENT IN INDONESIA: A CROSS-SECTIONAL FROM GLOBAL SCHOOL-BASED STUDENT HEALTH SURVEY 2015 - Maretalinia, Maretalinia; Suryani, Dyah; Edwin, Vebby Emilia; Suyitno, Suyitno; Nilasari, Nilasari (YCAB Publisher & IAKMI SULTRA, 2020)
Objective: The aim of this study was to estimate the prevalence and risk factors of underweight among adolescents in Indonesia in 2015.Methods: Cross-sectional data were analyzed from 7643 school-going adolescents from Indonesia, the